2014
DOI: 10.1093/geront/gnt147
|View full text |Cite
|
Sign up to set email alerts
|

What Does the Evidence Really Say About Culture Change in Nursing Homes?

Abstract: Nursing home culture change remains an evolving field. Although culture change has clear face validity, the current evidence does not give providers sufficient information for selecting interventions based on the expectation of improving outcomes. Rigorous research on implementation and outcomes of culture change is needed to determine the specific impact of culture change on quality and to provide guidance to providers and policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 31 publications
2
102
0
Order By: Relevance
“…29,30 Despite providing care to many at EOL, NHs largely focus on rehabilitation and restoring function. 31 Facilitating conversations about EOL contradicts this focus.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Despite providing care to many at EOL, NHs largely focus on rehabilitation and restoring function. 31 Facilitating conversations about EOL contradicts this focus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work described the association between quality of care and staffing patterns, 41e44 and quality of care and designation as a successful "culture change" site, 45,46 as well as the importance of nursing homes as an end-of-life setting. 4,38,43,47 However, no reports have focused explicitly on associations between organizational context and symptom burden or trajectories of symptom burden in the last year of life.…”
Section: Practice and Policy Implicationsmentioning
confidence: 99%
“…Some studies have identified adverse outcomes of culture change, such as a heightened fall risk among residents, 18, 19 but it does not appear that culture change practices lead to significant negative outcomes. 3 …”
Section: Introductionmentioning
confidence: 99%